TO THE SOLUTION OF A PROBLEM ON THE OSCILLATORY MOTION OF A BATAN MECHANISM - Dremova Nadezhda Vasilievna; Azimzhanov Sunnatillo (Journal Park Publishing, 2022)
On the basis of theoretical and experimental studies, a method is proposed for determining the dynamic characteristics of textile machine elements under the action of arbitrary dynamic loads in the form of an oscillogram.
Keywords: batan; batan mechanism; oscillations